Biometric based Access Control and Logging Module - Norazam, Nur Illyana (IRC, 2019)
Security has been playing huge role in many places such as offices, institutions, libraries and laboratories, to keep our data confidentiality so no unauthorized person can have access on them. This paper presents a design of biometric based access control and logging module for the usage of university level or any organisations and creating a prototype of the designed fingerprint biometric system. This system aims to strengthen the security of the current fingerprint access system by designing a system that stores the fingerprints of authorized users locally, and not on cloud, to prevent fingerprint tempering. The system is based on Arduino board which will communicate with the fingerprint sensor to obtain data of user and fingerprint is sensed by sensor and is validated for authentication. The prototype of biometric based access control and logging module can be used in practical situation.